Analisis Balik Stabilitas Lereng Disposal IPD (In Pit Dump) Utama Seam C pada area Pit B Selatan PT. Mifa Bersaudara, Aceh - Lazuardi, Fikram Khaykal (Program Studi Teknik Pertambangan, Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2025)
On the slopes of IPD Utama Seam C, the results of the data that have been validated through the SPT method approach show the results of FK = 4,388, this does not meet the requirements for back analysis. The results of the back analysis data show that the value of FK = 0.968 with changes in embankment material properties such as unit weight, friction angle, and cohesion which are very significant, this has a big influence on the slope safety factor, the biggest change is in the change in cohesion. The results of the evaluation data are based on entering the parameters of the back analysis using geometry after the landslide, and show the FK value = 1.018.